Microcredit, Technology Adoption and Economic Development of Rural Household - Jumbri, I.A; Nasir, N.N.M.; Sharif, S.M.; Zainudin, M.Z.; Ismail, A.F. (International Journal of Human and Technology Interaction (IJHaTI), 2020)
The main objective of this study is to investigate either Amanah Ikhtiar Malaysia (AIM) microcredit has led to the technology adoption and increase of rural household economy, particularly in household monthly income among its participants. This study was conducted in Melaka based on a sample of 200 participants. The findings of the study show that the AIM microcredit had a significant impact on technology adoption and increased the participant household monthly income in Melaka. The findings suggest that AIM microcredit is still relevant and plays an important role in increasing rural household monthly income, inculcate entrepreneurship among women and reduced poverty. Therefore, the Malaysian government should enact the relevant policies and give supports to enhance the effectiveness and outreach of microcredit.